Molecular detection of influenza A viruses and H5 subtype among migratory Amur falcons (Falco amurensis) and captive birds of prey. Issue 2 (17th February 2021) - El Zowalaty, Mohamed E.; DeBeauchmp, Jennifer; Jeevan, Trushar; Franks, John; Friedman, Kimberly; Pretorius, Rina; Young, Sean G.; Webster, Robert G.; Webby, Richard J.
Abstract: Influenza A viruses (IAVs) and Newcastle disease viruses (NDVs) are major human and animal health threats with geographic differences in prevalence, characteristics and host populations. Currently, there is sparse information on IAVs and NDVs in avian species in South Africa. Because raptors feed on live wild birds which are the reservoir hosts of IAVs and NDVs, we considered them a good sentinel for surveillance. Therefore, in addition to other resident birds of prey, migratory Amur falcons ( Falco amurensis ) were screened for IAVs and NDVs. Oropharyngeal and cloacal samples were collected from raptor species at three sampling sites in KwaZulu‐Natal Province and samples were screened for IAVs and NDVs using molecular and virus isolation methods. IAV‐positive samples were further screened for the presence of H5, H7 and H9 viruses. A total of 14 samples from 11 birds (45.8% of all sampled birds) were IAV positive with Ct lower than 36 in duplicate tests. Five out of 24 birds (20.8%) were positive for IAV RNA in duplicate testing, albeit at low concentrations. Among raptor samples, three out of 24 birds (12.5%) were positive for IAVs with viral RNA detected in both cloacal and oropharyngeal swabs. One IAV‐positive sample was also positive for H5 subtype (4.1%); all other samples were H5, H7 and H9 negative. Besides, all samples were NDV negative. Overall, our results support the development of more intensive and expanded influenza and other emerging virus studies in raptor species.